Review of the Fund's Income Position for FY 2012 and FY 2013-14. (Policy Papers; Policy Paper ;, 2012)
This paper reviews the Fund's income position for FY 2012 and FY 2013?14.1 The paper updates projections provided at the FY 2012 midyear review and proposes decisions for the current and next two financial years. These decisions include setting the margin for the rate of charge under the new Rule I-6(4) that the Executive Board adopted in December 2011.2 The new rule is based on principles endorsed by the Executive Board in April 2008 and that have guided decisions on setting the margin since FY 2009. Section II reviews the FY 2012 income position and main changes from the midyear projections; Section III makes proposals on the disposition of net income, and placement to reserves; Section IV discusses the margin on the rate of charge for FY 2013?14, the income outlook for that period, and projected burden sharing adjustments; and Section V reviews special charges.